Factors influencing safety work behaviour: a research framework - Abdul Rahim, Muhammad Akwa; Alias, Siti Noormi (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The study explores the moderating role of gender on individual-related and safety work behaviour focusing on the manufacturing industry. This paper applies the individual-related to examine the relationship between three factors perception of the minimum wage, work engagement and intention to leave toward safety work behaviour. This paper expected to offer future research and suggestion to the manufacturing managers to enhance their employees’ safety work behaviour practice and indirectly toward preventing workplace accidents.